Pengaruh Insentif Pajak, Sanksi Pajak dan E-Filing Terhadap Tingkat Kepatuhan Wajib Pajak Selama Covid-19 di Kantor Pelayanan Pratama Medan Petisah - Ridwan Syahputra Siregar; Rizqy Fadhlina Putri Putri (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the effect of tax incentives, tax sanctions, and e-filing on taxpayer compliance. The research population is all taxpayers of KPP Pratama Medan Petisah, using purposive sampling method with a sample of 95 taxpayers. The data analysis method used multiple linear regression analysis with SPSS 23.0 program. The results of the study indicate that the effect of tax incentives has a significant effect on taxpayer compliance. Tax sanctions have a significant effect on taxpayer compliance. e-filing has a significant effect on taxpayer compliance. Taken together, the effect of tax incentives, tax sanctions, and e-filing have a significant effect on taxpayer compliance.